Synthesis of 3-(4´´ -Substituted Phenyl)-5-(4´-Substituted Phenyl)- Δ2-Pyrazolines and Their Derivatives - Deshmukh, A.Y.; Raghuwanshi, P.B.; Doshi, A.G. (Asian Journal of Chemistry, 2010)
4-Substituted acetophenone (Ia–b) condenses with substituted benzaldehyde in ethanol in presence of pulverised KOH to give 4-substituted chalcone and 4´-substituted chalcone (IIa–d); (IIa–d) react with hydrazine hydrate in ethanol to give pyrazolines (IIIa–d). Pyrazolines (IIIa–d) react with acetic acid to form 1-acetyl pyrazoline (IVa–d), pyrazoline reacts with benzoyl chloride in pyridine to give 1-benzoyl pyrazoline (Va–d). Also pyrazoline reacts with sodium nitrite to give 1-nitroso pyrazoline (VIa–d). Characterisation and structural elucidation were done on the basis of chemical, analytical and spectral analysis.